PDE-5i Management of Erectile Dysfunction After Rectal Surgery: A Systematic Review Focusing on Treatment Efficacy - Notarnicola, Margherita (Am J Mens Health, 2020)
Erectile dysfunction (ED) is one of the main functional complications of surgical resections of the rectum due to rectal cancers or inflammatory bowel disease (IBD). The present systematic review aimed at revising ED management strategies applied after rectal resections and their efficacy in terms of improvement of the International Index of Erectile Function (IIEF) score. A literature search was conducted on Medline, EMBASE, Scopus, and Cochrane databases by two independent reviewers following the PRISMA guidelines. Randomized and nonrandomized controlled trials (RCTs, NRCTs), case-control studies, and case series evaluating medical or surgical therapies for ED diagnosed after rectal surgery for both benign and malignant pathologies were eligible for inclusion. Out of 1028 articles initially identified, only five met the inclusion criteria: two RCTs comparing oral phosphodiesterase type-5 inhibitor (PDE-5i) versus placebo; one NRCT comparing PDE-5i versus PDE-5i + vacuum erection devices (VEDs) versus control; and two before-after studies on PDE-5i. A total of 253 (82.7%) rectal cancer patients and 53 (17.3%) IBD patients were included. Based on two RCTs, PDE-5i significantly improved IIEF compared to placebo at 3 months (SMD = 1.07; 95% CI [0.65, 1.48]; p < .00001; I(2) = 39%). Improved IIEF was also reported with PDE-5i + VED at 12 months. There is a paucity of articles in the literature that specifically assess efficacy of ED treatments after rectal surgery. Many alternative treatment strategies to PDE-5is remain to be investigated. Future studies should implement standardized preoperative, postoperative, and follow-up sexual function assessment in patients undergoing rectal resections.